DEVELOPMENT OF STARTUP BUSINESS THROUGH THE UTILIZATION OF TECHNOLOGICAL INNOVATION ON THE E-COMMERCE PLATFORM AT KEDAI NAKAMA - Nuraina Awin Saputri; Muhammad Rakib; Agus Syam; Muhammad Jufri; Sumiati Tahir (Adisam Publisher, 2025)
This study aims to develop the Kedai Nakama startup business through the utilization of e-commerce technology innovation based on the Odoo web platform. The subjects of this study consisted of the owner of the Kedai Nakama Business and four employees. The research method used was qualitative with a Research and Development (R&D) approach using the 4D model (Define, Design, Develop, Disseminate). Data were collected through observation methods, interview methods, and documentation. The results of the study indicate that the implementation of an e-commerce platform designed according to customer needs and desires can contribute to increased sales and is able to improve market access, operational efficiency, and customer experience. Through interactive web design and complete features, such as landing pages, product catalogs, and shopping carts, Kedai Nakama managed to increase revenue in the three months after implementation. This study provides a practical contribution to the development of digital technology-based businesses. With the implementation of this website, Kedai Nakama can reach a wider market, increase marketing effectiveness, and compete better in the digital era. The website is not only a promotional tool, but also a modern solution to improve customer experience and increase sales significantly.